In-situ analysis of chemical expansion and stability of SOFC cathodes. Issue 1655 (6th May 2014) - Dragan, Mirela; Misture, Scott
ABSTRACT: In this work high-temperature X-ray diffraction has been used to investigate thermal and chemical expansion as well as overall phase stability for various cathode materials: Ba0.5 Sr0.5 Co0.8 Fe0.2 O3 (BSCF), La0.3 Sr0.7 CoO3 (LSC37), La0.6 Sr0.4 CoO3 (LSC64) and La0.6 Sr0.4 Fe0.8 Co0.2 O3 (LSCF), as a function of temperature in reducing conditions. When perovskites materials are under a low oxygen partial-pressure condition, the lattice parameter and overall dimension increase. Their chemical expansion has comparable values. From the viewpoint of the stability of these phases, the high-temperature X-ray diffraction results indicate no phase decomposition can be one of the reasons for material failure at the current experimental oxygen partial pressure. LSF is most stable, while LSC and LSCF form oxygen vacancy-ordered phases and then decompose when heated to 1000°C under atmospheres with pO2 as low as 10 -5 atm.